Effects of Overweight and Obesity on Hypertension in Adolescents: A Meta-Analysis - Nurussyifa Afiana Zaen; Didik Tamtomo; Burhannudin Ichsan (Masters Program in Public Health, 2023)
Background: Hypertension is currently starting to show a trend in prevalence that continues to increase at a younger age and is a major cause of premature death in the world. In adolescents, hypertension is more common who are overweight or obese. This study aims to examine the effect of overweight and obesity on the incidence of hypertension in adolescents using a meta-analysis.Subjects and Method: Meta-analysis was carried out using the PRISMA flow chart and the PICO model. Population: adolescents aged 10 to 19 years. Intervention: overweight and obesity. Comparison: normoweight. Outcome: hypertension). The databases used are PubMed, Science Direct, Springer Link, and Google Scholar with the keywords (hypertension OR